Futsal Training Innovation: Diamond Passing as a Strategy to Improve Futsal Students' Passing Accuracy - Nurmaharani, Sita Dwi; Septianingrum, Kartika; Kusuma, Wening Sekar; Utomo, Andy Widhiya Bayu (UNIVERSITAS NEGERI MAKASSAR, 2025)
This research aims to determine the effect of diamond passing training on passing accuracy among futsal extracurricular students at SMA Negeri 2 Ngawi Taruna Indonesia. This type of research uses an experimental method with a pretest-posttest control group design. The population in this study was 25 students, and the sample used was 20 students selected using a purposive sampling technique with certain criteria, each divided into 10 control groups and 10 experimental groups. The research was conducted for three months, from January to March 2025. The instrument used was a passing accuracy test using a small goal as a target. The data obtained were analysed using prerequisite tests, namely the normality test and homogeneity test, followed by hypothesis testing using the paired sample t-test. The research results show that there is a significant difference between the pretest and posttest results, with a significance value of 0.000 <0.05. This proves that diamond passing practice has a significant effect on increasing students' passing accuracy. This exercise is effective in improving coordination, accuracy and speed of decision making in futsal games. Thus, diamond passing training can be used as an alternative method for practising basic passing techniques in futsal extracurricular activities in the school environment.